Magazine dreams [videorecording (DVD)] - Bynum, Elijah; Majors, Jonathan, 1989-; Page, Harrison; Harris, Harriet Sansom, 1955-; Bennett, Haley, 1988-; O'Hearn, Michael (Actor); Paige, Taylour, 1990-; Stryker, Bradley, 1977-; Cackowski, Craig; Valicenti, Sonny; Hill, Jason (Composer); Arkapaw, Adam (Briarcliff Entertainment LLC, 2025)
Killian Maddox is a troubled young man obsessed with becoming a bodybuilding star. Looking after his ailing grandfather and working a dead-end job, his intense drive and volatile temper push him toward self-destruction.